2010
DOI: 10.1021/ci100081j
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Binary Classification QSAR Models Based on 4D-Fingerprints and MOE Descriptors for Prediction of hERG Blockage

Abstract: Blockage of the human ether-a-go-go related gene (hERG) potassium ion channel is a major factor related to cardiotoxicity. Hence, drugs binding to this channel have become an important biological end point in side effects screening. A set of 250 structurally diverse compounds screened for hERG activity from the literature was assembled using a set of reliability filters. This data set was used to construct a set of two-state hERG QSAR models. The descriptor pool used to construct the models consisted of 4D-fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 49 publications
2
63
0
Order By: Relevance
“…Most of the previously available hERG computational models are ligand-based but since these rely mainly on the existence of structural similarities between the tested drug candidate and previously reported known hERG blockers, these models have limited value in the frequent case of a novel drug structure (Aronov and Goldman, 2004;Coi et al, 2006;Du-Cuny et al, 2011;Ekins et al, 2002;Keseru, 2003;Song and Clark, 2006;Su et al, 2010;Yoshida and Niwa, 2006). Producing a reliable hERG ion channel structure-based model to directly test drug binding (Broccatelli et al, 2012;Du-Cuny et al, 2011) has therefore been of high priority but in the absence of a hERG crystal structure, this has been limited to creating homology models that have excluded a large portion of the hERG channel and which display very limited conformational flexibility (Boukharta et al, 2011;Di Martino et al, 2013;Farid et al, 2006;Osterberg and Aqvist, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previously available hERG computational models are ligand-based but since these rely mainly on the existence of structural similarities between the tested drug candidate and previously reported known hERG blockers, these models have limited value in the frequent case of a novel drug structure (Aronov and Goldman, 2004;Coi et al, 2006;Du-Cuny et al, 2011;Ekins et al, 2002;Keseru, 2003;Song and Clark, 2006;Su et al, 2010;Yoshida and Niwa, 2006). Producing a reliable hERG ion channel structure-based model to directly test drug binding (Broccatelli et al, 2012;Du-Cuny et al, 2011) has therefore been of high priority but in the absence of a hERG crystal structure, this has been limited to creating homology models that have excluded a large portion of the hERG channel and which display very limited conformational flexibility (Boukharta et al, 2011;Di Martino et al, 2013;Farid et al, 2006;Osterberg and Aqvist, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, molecular features that in general negatively correlate with block include the presence of polar entities (156,447,569,638,703) and hydrophilic groups close to hydrophobic regions of the drug (562,569). On this note, distances between features (such as proximity between nonpolar atoms or between hydrogen bond donors and polar groups) may also be significant factors (569,599).…”
Section: Herg K ϩ Channelsmentioning
confidence: 99%
“…Recently we have shown that merging 1D through 4D molecular descriptor sets into a single trial descriptor pool leads to multi-class continuous and classification QSAR models that are superior for the prediction of hERG cardiotoxicity when compared to models from the corresponding segregated descriptor sets. [36,37] The transport of organic compounds through lipid assemblies of the stratum corneum for transdermal drug delivery applications has also been modeled using multiple classes of descriptors. [38] The trial descriptor pool consisted of intermolecular interactions between a membrane (monolayer of DMPC) and the penetrant as well as intramolecular (1D and 2D molecular descriptors; classic descriptors) features of only the penetrant.…”
mentioning
confidence: 99%